A Study in the Farm Investment and Income Pattern of Farm Families in Arid Zone of Rajasthan - Kalla, Jagdees C; Vyas, D L (Annals of Arid Zone, 2016)
Investment in Farm assets for augmenting production in Indian agricultural sector is one of the principal themes for perennial discussion among social scientists. This paper attempts at quantifying the relationships of existing Farm por-folios of farm families classified on the basis of size of holding. Through this articles authors propose that size of Farm is one of the important determinants for incomes and Investments in arid areas. Farm Investment under arid conditions is couched in traditional set up of investing possibilities. Although Farm Investments categries as they are, fail to explain statistical variance in income levels significantly, nevertheless, succeed in contributing, in an important way, to augment the agricultural incomes. Finally, it is established that new opportunity for increased Farm Investment donot exist in conducive way owing to hostile agro-climatic situations.